Research on location privacy protection of mobile terminals for maritime monitoring sensor networks - Xin SU; Su JIANG; Yiqing ZHOU (物联网学报)
Mobile edge computing can support various maritime applications with high reliability and low delay.However, many security problems in computing task offloading exist.The risk of location privacy leakage of maritime mobile terminals during task offloading was analyzed and quantified.The related location privacy protection model was established and a dynamic cache and spatial cloaking-based location privacy protection (DS-LPP) algorithm was proposed.Simulation results show that DS-LPP algorithm has better performance of constructing anonymous space and selecting relay node than traditional algorithms while protecting the location privacy of maritime mobile terminals.Therefore, the DS-LPP algorithm can be effectively applied to maritime monitoring sensor network with relatively scanty communication and computing resources, and ensure the continuity of location privacy protection.